CONCEPT OF INTERRELATIONSHIP BETWEEN MANAS (PSYCHE) & SHARIRA (SOMA) W.S.R. TO AYURVEDIC TREATMENT - R.S, *Dhimdhime; K.B, Pawar; D.T, Kodape; S.R, Dhimdhime; Baghel, Prashant (International Journal of Ayurveda and Pharma Research, 2017)
The Manas (Psyche), soul and Sharira (Soma) are the tripods for existence of life. In other words, life is sum of soma, senses (Indriya), psyche and soul (Atma). Ayurveda considers mind and body as two pathways or substrata for manifestation of disease. Mind has in it three constituents or tendencies in Satvam (Balance), Rajas (Arrogance) and Tamas (Indolence). Later two are reactive tendencies which vitiate the mind leading to an emotional imbalance, culminating in a physiological disturbance. Rajas and Tamas hence are termed as two Dosha of mind, Likewise the three biohumors Vata, Pitta and Kapha, which are termed as Doshas of the body. Vitiate the body leading to metabolic disturbance which ultimately culminates in a somatic disturbance. Psyche and soma are always interrelated. Soma is combination of three Doshas, seven Dhatus and three Malas as well as Manas, and they all have their own way of functioning. They interact and influence each other jointly venture in the manifestation of a very large group of disorder aptly known as psychosomatic disorder, The so-called â€œpureâ€ disorder arising out of singular involvement of either psyche or soma infact very few. Since ancient time Ayurveda has already focused on basics of interrelationship between Psyche and Soma, while mentioning Sattvavajaya Chikitsa (Psychotherapeutic Procedure). To reach an appropriate Ayurvedic management of psychosomatic disorder an individual should approach by understanding the concept of interrelationship of Psyche and Soma. Hence Ayurveda adopts a comprehensive psychosomatic approach by and large for the management of disease.